2020
DOI: 10.1111/jcmm.15617
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic31P‐magnetic resonance spectroscopy identified the impact of melatonin‐pretreated mitochondria in acute liver ischaemia‐reperfusion injury

Abstract: Acute liver ischaemia‐reperfusion injury (IRI), commonly encountered during liver resection and transplantation surgery, is strongly associated with unfavourable clinical outcome. However, a prompt and accurate diagnosis and the treatment of this entity remain formidable challenges. This study tested the hypothesis that 31P‐magnetic resonance spectroscopy (31P‐MRS) findings could provide reliable living images to accurately identify the degree of acute liver IRI and melatonin‐pretreated mitochondria was an inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Studies on mitochondrial transplantation have also been conducted in other experimental models including acute limb ischemia [ 45 ], lung IRI [ 46 ], spinal cord injury [ 47 ], and acute liver injury [ 48 ] models. Orfany et al [ 45 ] used a C57BL/6 J male mouse acute limb ischemia model to compare the impact of dose-dependent mitochondrial injection (1 × 10 6 , 1 × 10 7 , 1 × 10 8 , and 1 × 10 9 mitochondria/g muscle) after IRI with f-Rhodamine 6G-labeled mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on mitochondrial transplantation have also been conducted in other experimental models including acute limb ischemia [ 45 ], lung IRI [ 46 ], spinal cord injury [ 47 ], and acute liver injury [ 48 ] models. Orfany et al [ 45 ] used a C57BL/6 J male mouse acute limb ischemia model to compare the impact of dose-dependent mitochondrial injection (1 × 10 6 , 1 × 10 7 , 1 × 10 8 , and 1 × 10 9 mitochondria/g muscle) after IRI with f-Rhodamine 6G-labeled mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…They found that mitochondrial transplantation significantly reduced neuronal apoptosis and improved locomotor function in rats with spinal cord ischemia by suppressing oxidative stress and endoplasmic reticulum (ER) stress [ 47 ]. Ko et al [ 48 ] investigated whether 31 P-magnetic resonance spectroscopy ( 31 P-MRS) could accurately identify the protective effects of transplanting melatonin-pretreated mitochondria (m-Mito) on acute liver IRI in rats. At 72 h after acute liver IRI, 31 P-MRS showed that the hepatic levels of ATP and NADH were significantly higher in the m-Mito group than in the IRI group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the limited sample size and short follow-up, there was no data on the effect of melatonin on the recurrent stroke and other post-operative complications. Although the clinical evidence of melatonin treating CAS-induced cerebral I/R injury is limited, its protective effects of targeted organs against I/R injury in the heart [14], intestine [47], liver [48], and kidney [49] have been demonstrated elsewhere, which indirectly supported the potential benefit of melatonin, alleviating cerebral I/R injury after CAS revascularization.…”
Section: Melatonin and Cerebral Ischemia/reperfusion Injurymentioning
confidence: 93%
“…Moskowitzova et al [26] isolated syngeneic mitochondria from gastrocnemius muscle of C57BL/6J mice. Ko et al [40] reported that mitochondrial isolation was performed with 3 g of rat liver samples.…”
Section: Tissue-cell Sources and Isolation Process For Mitochondrial Transplantationmentioning
confidence: 99%